Structures and magnetic properties of two heterometallic Cu(ii)–Cd(ii) polymers exhibiting antiferromagnetic ordering. Issue 13 (7th March 2022) - Li, Zhong-Yi; Zhang, Ran; Zhu, Peng-Yu; Zhang, Chi; Wu, Dong-Qing; Zhai, Bin
Abstract : Two heterometallic Cu(ii )–Cd(ii ) polymers (1 and 2 ) with a 2D layer or 1D chain structure were obtained and their magneto-structural correlations were discussed, and 1 displayed antiferromagnetic ordering at lower temperature. Abstract : Two novel heterometallic Cu(ii )–Cd(ii ) coordination polymers, two-dimensional (2D) [Cu2 Cd(MMA)2 (NTA)2 (H2 O)2 ] n (1 ) and one-dimensional (1D) {[CuCd(MMA)2 (H2 O)6 ]·4H2 O} n (2 ), were synthesized with methylmalonic acid (H2 MMA) and nicotinic acid (HNTA) as mixed reactants under the conditions of 100 °C and room temperature, respectively. Complex 1 has a 2D layer structure consisting of the tetranuclear [Cu2 Cd2 ] cluster-based 1D chain unit and NTA − linker. 2 exhibits a 1D chain structure with the Cu 2+ and Cd 2+ ions alternately bridged by the MMA 2− ligand. Magnetic studies show that the magnetic interactions for the neighboring Cu 2+ ions are both antiferromagnetic within and between the [Cu2 Cd2 ] cluster of the 1D chain in 1 ( J d = −1.39(1) cm −1 and J c = −1.77(1) cm −1 ) and there is predominantly ferromagnetic coupling in the 1D chain of 2 ( J = 4.96(1) cm −1 ). Furthermore, 1 displayed antiferromagnetic ordering at lower temperature with T N = 4.0 K.